Prevalence and Clinical Characteristics of Temporomandibular Disorders in Adults: An Epidemiological Study in the Mediterranean Region of Türkiye - Yavuz, Esra; Yardimci, Selmi; Tercanli, Humeyra (UI Scholars Hub, 2023)
The prevalence and clinical characteristics of temporomandibular disorders (TMD) in the Mediterranean region of Türkiye have not yet been thoroughly investigated. Objective: This study aimed to determine the prevalence and severity of TMD in a sample of the population in this region and to characterize the clinical findings related to TMD. Methods: Four hundred and one participants were included in this study. “Presence of TMD” in the participants was evaluated using the Fonseca Anamnestic Index. Through clinical examination, the findings in the participants were classified as limited mouth opening, deviation, temporomandibular joint (TMJ) sounds, TMJ pain, and muscle pain. Results: The prevalence of TMD was found to be 66.8%, with “Mild TMD” being the most frequent diagnosis among the participants. Clinical findings related to TMD were detected in 48.6% of the participants, and TMJ sounds were the most common clinical finding. TMD was most commonly found in participants over the age of 52, and clinical findings related to TMD were most common in participants between the ages of 25 and 38. In addition, a relationship was found between “Presence of clinical findings” and the gender and age of the participants (p < 0.001 for both comparisons). Conclusion: The results show that females may be more prone to TMD than males. During clinical examinations, it should be considered that “Presence of clinical findings” may be related to gender and age.